YIELD FORMATION OF OYSTER MUSHROOM UNDER THE INTENSIVE METHOD OF GROWING - Вдовенко, С. А. (Scientific Progress & Innovations, 2013)
Peculiarities of two strains of oyster mushroom production on the substrate from wheat, barley, pea and straw are examined. The peculiarities of fungus fruit bearing and getting a marketable production in conditions of protected soil are determined. It is defined that the pea straw should be applied for the preparation of substrate while growing oyster mushroom; the above mentioned substrate is characterized by the rapid onset of the fungus growth and development phases, it provides general yield capacity and improves the marketability of products.